2006
DOI: 10.1073/pnas.0511099103
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of aging on fluid intake in response to hypovolemia, hypertonicity, and hormonal stimuli in Munich Wistar rats

Abstract: A significant proportion of aged humans may have impaired thirst and inadequate fluid intake after a period of fluid deprivation. We have studied the water drinking responses, relative to body weight, of Munich Wistar (MW) rats in response to osmotic, hypovolemic, dehydrational, and angiotensin (Ang)-related stimuli as they aged from 3 to 24 months. Young 3-months-old (m.o.) rats had the largest daily fluid intakes and drinking responses to hypertonic and dehydrational stimuli, suggesting that they have accent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…We (40) and others (25) find that aged rats drink less than young rats to peripherally administered hypertonic NaCl solution, but this finding is also not consistent for all laboratories (25,34). Our previous work (40) indicated that 20-mo-old Brown Norway rats are refractory to osmotic loads producing 2-4% increases in estimated plasma osmolality, but we have not used smaller loads or older rats.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…We (40) and others (25) find that aged rats drink less than young rats to peripherally administered hypertonic NaCl solution, but this finding is also not consistent for all laboratories (25,34). Our previous work (40) indicated that 20-mo-old Brown Norway rats are refractory to osmotic loads producing 2-4% increases in estimated plasma osmolality, but we have not used smaller loads or older rats.…”
mentioning
confidence: 68%
“…There are conflicting reports about whether old rats drink less in response to hypotension. For example, old rats have been found to drink less after subcutaneous injections of isoproterenol compared with young rats (24,34,37), although not always (25,34). These previous studies did not record arterial pressure or control for differences in arterial pressure that may occur with aging (24,25,34,37).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Stimulation of vascular ␤ 2 -adrenergic receptors causes vasodilation and reductions in arterial pressure, which reflexively increase HR and renin secretion through baroreceptor mechanisms (21, 26). The water drinking response is a result of isoproterenol-induced hypotension and renin secretion (21,26,31).Several studies have used isoproterenol to examine agerelated declines in drinking by rats (24,25,34,35). However, the relative contributions of the ␤ 1 -and ␤ 2 -adrenergic receptor subtypes to age-related drinking have not been examined.…”
mentioning
confidence: 99%
“…Several studies have used isoproterenol to examine agerelated declines in drinking by rats (24,25,34,35). However, the relative contributions of the ␤ 1 -and ␤ 2 -adrenergic receptor subtypes to age-related drinking have not been examined.…”
mentioning
confidence: 99%